2013
DOI: 10.1111/bjd.12083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atopic dermatitis and loss-of-function mutations in the filaggrin gene on the development of occupational irritant contact dermatitis

Abstract: Our results indicate that both FLG mutations and AD increase the risk of ICD. Individuals with concurrent FLG mutations and AD are at the highest risk of developing ICD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 53 publications
3
81
1
8
Order By: Relevance
“…The mechanisms for increased irritancy in AD are likely multifactorial. A German case-control study of patients with occupational irritant contact dermatitis (ICD) and healthy controls found that patients with either history of AD or common FLG null variants had significantly higher risk of ICD; however, those with both AD and FLG variants were at highest risk of ICD [62]. These results suggest that FLG variants may play an important role but are not the only mechanism.…”
Section: Irritants and Pruritogensmentioning
confidence: 99%
“…The mechanisms for increased irritancy in AD are likely multifactorial. A German case-control study of patients with occupational irritant contact dermatitis (ICD) and healthy controls found that patients with either history of AD or common FLG null variants had significantly higher risk of ICD; however, those with both AD and FLG variants were at highest risk of ICD [62]. These results suggest that FLG variants may play an important role but are not the only mechanism.…”
Section: Irritants and Pruritogensmentioning
confidence: 99%
“…[5,7,11,12]. Other factors can also contribute to the onset of irritant CD -perspiration from glove occlusion or prolonged contact with an alkaline, skin sensitivity, prior skin damage, or an atopy such as atopic dermatitis (AD) [13]. In diagnostics of rubber glove allergies, the most common tests are skin prick tests (SPTs) and/or latex-specific IgE assay to determine immediate-type allergies to Hevea brasiliensis, and patch tests to determine delayed-type allergies to rubber additives [1,14,15].…”
mentioning
confidence: 99%
“…According to the literature, it could be suggested that sex (female), atopy, and wet work should be considered as markers of poor prognosis primarily for ICD. Wet work is known as a highly important occupational and non-occupational skin irritant and is performed mainly by female workers [3], while atopy in the form of childhood or adult atopic eczema or some other atopic disease is undoubtedly the most important independent risk factor in the development of ICD [4,10,30]. It could be stated that predictors of ACD prognosis have not yet been clearly defined, but there is agreement about the influence and interactions of genetic and environmental factors on the development and course of ACD [1,22], with a thus far more clearly presented influence of environmental factors [3,31].…”
Section: Discussionmentioning
confidence: 99%
“…While atopy and FLG null mutations are clearly defined as independent risk factors in the development of ICD [4,10,30], their role in the development of ACD is controversial. Up to now, 3 studies have suggested a risk of developing contact allergy to nickel in subjects with FLG null mutations, indicating that a damaged skin barrier in persons with FLG null mutations can facilitate the penetration and presentation of nickel to antigen-presenting cells in the skin resulting in the development of easier and earlier sensitization [7,8,36].…”
Section: Discussionmentioning
confidence: 99%